Indirect assessment of the fusion properties of choline chloride from solid-liquid equilibria data - Fernandez, Luis (2018)
The temperature and enthalpy of fusion of choline chloride -[Ch]Cl- are not directly measurable since this compound decomposes upon melting. Yet, given the wide use of this compound in the preparation of deep eutectic solvents (DES), its thermophysical fusion properties are very important for a better understanding of these mixtures and the thermodynamic description of their solid-liquid phase diagrams. In this work, the fusion properties of choline chloride were estimated using the solubility curves of choline chloride in ten different ionic compounds, forming simple binary eutectic mixtures with quasi-ideal liquid phases. Experimental solid-liquid equilibria data for these systems -[Ch] Cl + ionic compounds- were measured, and the ideality of the systems assessed through the quantification of the activity coefficients and their comparison in each pair of binary solutions. The values estimated for the fusion properties of choline chloride are T fus,[Ch]Cl = 597 ± 7 K and Δ fus H [Ch]Cl = 4300 ± 600 J mol −1 . These were additionally checked by thermodynamic consistency tests and by the prediction of the solid-liquid curves with COSMO-RS model. The results obtained with both procedures allow us to guarantee the usefulness and robustness of the estimated data.